Rapid identification of pathogenic Leptospira species (Leptospira interrogans, L. borgpetersenii, and L. kirschneri) with species-specific DNA probes produced by arbitrarily primed PCR. - Letocart, M (1997)
Arbitrarily primed PCR (AP-PCR) assays can be used to discriminate between species of Leptospira. Comparative analysis of the fingerprints obtained from representative sets of serovar reference strains of Leptospira interrogans sensu stricto, L. borgpetersenii, and L. kirschneri and the reference strains of the other Leptospira spp. revealed species-specific DNA fragments. These species-specific sequences were reamplified in order to produce digoxigenin-11-dUTP-labeled genomic DNA probes that could be used to identify Leptospira species. Three probes (specific for L. interrogans sensu stricto, L. borgpetersenii, and L. kirschneri) were selected and tested with 72 representative serovar reference strains, all of which had previously been studied by DNA-DNA hybridization. The two techniques were in general agreement, and hybridization with AP-PCR-derived probes was shown to be a useful approach for rapid species determination of leptospires, without the prior need for DNA sequence information. These nonradioactive probes can be used to identify Leptospira species in nonspecialized laboratories, and this should contribute to a better knowledge of the molecular epidemiology of leptospirosis.